Growth pattern and stock assessment of Jinga shrimp Metapenaeus affinis (H. Milne Edwards, 1837) (Decapoda, Penaeidae) from the southeastern Mediterranean of the Egyptian coasts - Fatma A. Abdel Razek; Evelyn Ragheb; Rabab S. El-Deeb; Hamdy Omar Ahmed (Egyptian Journal of Aquatic Research, 2022)
A total of 1457 random specimens of the newly established population of Metapenaeus affinis was collected monthly from the shrimp commercial catch at Boughaz El-Maadiyah landing center (Mediterranean Sea, Egypt) during the period from July 2020 to June 2021. This study aims to shed light on the growth pattern and stock assessment of this newly established species. The results showed that the catch of M. affinis varied in lengths between 5.4 cm and 16.0 cm TL. At length 13.5 cm, the population was composed of 100% females. The test of the allometric coefficients “b” of the total length (TL) – carapace length (CL) relationship showed negative allometry growth for males, females, and sexes combined. The values of “b” for the length-weight relationship reflected isometric growth for males, and a pattern of positive allometric growth was shown for females and sexes combined. The overall sex ratio (F:M) was 1.00:0.58 and the Chi-square test reflected high significant differences (χ2 = 100.68; df = 1; P < 0.01). Five cohort groups representing 2 yr for females and four cohort groups representing 1+yr for males were identified by Bhattacharya's method. For combined sexes, the growth parameters were L∞ = 19.849 cm, K = 0.242, and to = −0.872. The study of fishery parameters revealed that M. affinis population was still unexploited (Ecur. = 0.38). Further studies are recommended to shed lights on its spawning and nursery grounds in the Egyptian waters. The study of the reproductive biology for this shrimp species is also recommended.